Euodiae Fructus: a review of botany, application, processing, phytochemistry, quality control, pharmacology, and toxicology - Hao, Yule; Qi, Jiawen; Huang, Xinggui; Liu, Chenhao; Liu, Yi (Frontiers in Pharmacology, 2025)
Euodiae Fructus (EF) is the dried and nearly ripe fruit of Euodia rutaecarpa, first recorded in Shen Nong’s Herbal Classic. EF is a versatile Traditional Chinese Medicine (TCM) known for the effects of dispelling colds and alleviating pain, suppressing adverse qi to relieve vomiting, and boosting yang to mitigate diarrhea. However, it should be noted that EF possesses mild toxicity. In TCM prescriptions, EF is employed to treat various ailments, including abdominal pain, diarrhea, chronic non-atrophic gastritis, irritable bowel syndrome, and primary dysmenorrhea. This review collected the literature published before September 2024 on EF. An exhaustive analysis of EF literature was conducted utilizing multiple sources, namely classic TCM books and various scientific databases like Web of Science, PubMed, Elsevier, ACS, ResearchGate, Google Scholar, and Chinese National Knowledge Infrastructure. So far, more than 300 metabolites have been extracted and identified from EF, exhibiting various pharmacological effects, such as cardiovascular protection, gastrointestinal protection, neuroprotection, anti-inflammation, analgesia, anti-tumor, glucose and lipid metabolism regulation, etc. It also exhibits diverse toxicological properties and poses specific toxic risks to the liver, heart, and kidney. Nonetheless, research is scarce regarding the toxicology of EF, especially on its cardiotoxicity and nephrotoxicity. Further in-depth research is necessary to explore the mechanisms underlying EF’s pharmacological and toxicological mechanisms and to develop strategies for quality control and toxicity mitigation. The toxicity of EF can be reduced by processing, but this aspect is rarely discussed, and the quality control needs to be further standardized. Evodiamine, rutaecarpine, and limonin are the effective metabolites of EF and are also one of the causes of EF toxicity. The pharmacological effects of evodiamine and rutaecarpine have been intensely studied, but there are few studies on limonin and other metabolites of EF. Therefore, this paper focuses on the botanical characteristics, traditional applications, processing methods, phytochemistry, quality control, pharmacology, and toxicology of EF. We hope this paper provides a theoretical basis for the future high-value and high-connotation development of EF.